1987
DOI: 10.1111/j.1939-0025.1987.tb03535.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors in fatal childhood asthma.

Abstract: A review of three recent cases of death due to childhood asthma revealed consistent themes of depression, emotional precipitation of attacks, unsupportive families, and a tendency to deny asthma symptoms. Possible psychosomatic mechanisms are identified as potentially important for the interaction of emotions and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 21 publications
0
21
1
1
Order By: Relevance
“…Given the psychological and behavioural component associated with asthma and its management,3 26 the findings of our study are not entirely unexpected, at least with regard to use of major tranquillisers. Unlike previous reports linking asthma mortality with depression, especially in children,27 28 29 our study did not show an increased risk among users of antidepressants, possibly on account of age differences in study populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Given the psychological and behavioural component associated with asthma and its management,3 26 the findings of our study are not entirely unexpected, at least with regard to use of major tranquillisers. Unlike previous reports linking asthma mortality with depression, especially in children,27 28 29 our study did not show an increased risk among users of antidepressants, possibly on account of age differences in study populations.…”
Section: Discussioncontrasting
confidence: 99%
“…The group with severe asthma but good adherence showed a level of psychiatric morbidity inbetween the highest and lowest levels. In another study 26 patients (68.5%) reported symptoms of anxiety and 25 (65.8%) patients reported symptoms of depression (18) In a study, Fritz et al (19) found a significant difference in FEV 1 and FEV 1 /FVC values between asthma patients with and without depressive symptoms, and suggested that this may be associated with a common biological pathway between asthma and depression. There are many studies suggesting that treatment of depression and anxiety in patients with asthma improve control of the disease (20,21).…”
Section: Discussionmentioning
confidence: 98%
“…Pediatricians are now aware of the importance of psychosocial factors in asthma (Warner, Gotz, Landau, et al, 1989, 1992). This knowledge is based on several retrospective studies about children who died from asthma (Fritz, Rubinstein, & Lewiston, 1987; Strunk, 1987, 1989; Strunk et al, 1985; Teitz, Kahlstrom, & Cardiff, 1975). These studies concluded that psychological factors were at play in fatal or nearly fatal asthma.…”
Section: Introductionmentioning
confidence: 99%